1989
DOI: 10.3354/meps053227
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium levels in oystercatcher Haematopus ostralegus from the German Wadden Sea

Abstract: Cadmium levels of ludney and liver tissues of 150 oystercatcher Haematopus ostralegus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…However, Stock et al (1989) reported that cadmium levels in Eurasian oystercatcher (Haematopus ostralegus) from the German Wadden Sea had levels of cadmium of 180 ng/g, compared to 91 ng/g in the present study. Selenium in the flight feathers of Eurasian oystercatcher averaged from 10,000 to 30,000 ng/g (Goede, 1991), compared to 8,000 ng/g for the oystercatchers from Prince William Sound.…”
Section: Geographical Comparisonsmentioning
confidence: 46%
“…However, Stock et al (1989) reported that cadmium levels in Eurasian oystercatcher (Haematopus ostralegus) from the German Wadden Sea had levels of cadmium of 180 ng/g, compared to 91 ng/g in the present study. Selenium in the flight feathers of Eurasian oystercatcher averaged from 10,000 to 30,000 ng/g (Goede, 1991), compared to 8,000 ng/g for the oystercatchers from Prince William Sound.…”
Section: Geographical Comparisonsmentioning
confidence: 46%
“…The literatures used for the regression analyses for Hg in muscle and kidney are shown in the legend of Figure 5. For the analyses of Hg in liver, Mn in kidney, and Cd in liver and kidney, the data of Stock et al [39], Lock et al [40], Llacuna et al [35], and Augspurger et al [41] also were used. The relationships obtained were as follows: …”
Section: Resultsmentioning
confidence: 99%
“…Cadmium causes sublethal and behavioral effects at lower concentrations than mercury and lead (Eisler 1985). Effects of cadmium contamination include kidney damage, altered behavior, suppression of egg production, egg-shell thinning, and testicular damage (Furness 1996;Stock et al 1989). Scheuhammer (1987) reported background levels of cadmium at \3 lg/g dry weight in liver.…”
Section: Discussionmentioning
confidence: 98%